2020
DOI: 10.1088/1361-6455/ab8949
|View full text |Cite
|
Sign up to set email alerts
|

Steady states of a driven dissipative dipolar XXZ chain

Abstract: We study theoretically a driven dissipative one-dimensional XXZ spin−1/2 chain with dipole coupling and a tunable strength of the Ising and XY interaction. Within a mean-field approximation, we find a rich phase diagram with uniform, spin density wave, antiferromagnetic and oscillatory phases, as well as regions of phase bistability. We study the phase diagram of small quantum systems using exact diagonalisation, and compare the results to the mean-field theory. We find that while expectation values only captu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Bistability in driven-dissipative models usually means the presence of two possible stationary states of the system that can be distinguished by local observable measurements. Although on the level of the meanfield approximation it can be easily established whether or not it exists, its actual existence, in particular in low-dimensional strongly interacting systems, remains quite controversial with both theoretical and experimental work reporting differing conclusions [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The existing approaches usually rely on sophisticated theoretical techniques for including perturbations of finite-size corrections to the mean-field or large scale efficient numerical simulations such as t-DMRG [8] or projected entangled pair states (PEPS) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Bistability in driven-dissipative models usually means the presence of two possible stationary states of the system that can be distinguished by local observable measurements. Although on the level of the meanfield approximation it can be easily established whether or not it exists, its actual existence, in particular in low-dimensional strongly interacting systems, remains quite controversial with both theoretical and experimental work reporting differing conclusions [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The existing approaches usually rely on sophisticated theoretical techniques for including perturbations of finite-size corrections to the mean-field or large scale efficient numerical simulations such as t-DMRG [8] or projected entangled pair states (PEPS) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has already been demonstrated that the cooperative dynamics of two interacting (dipole-dipole) two-level atoms can result in the inhibition of their fluorescence -a phenomenon attributed to the coupling between the symmetric and antisymmetric collective states [12]. The emergence of collective steady states of driven two-level systems coupled by their mutual dipolar interactions has received considerable interest in the recent years [13][14][15][16]. In this work, our aim is to show that the prethermal phase can also appear in the dynamics of an interacting two-qubit system, coupled to a thermal bath if we consider the cross-correlated dissipators from the drive and inter-qubit interactions.…”
mentioning
confidence: 99%